Herpes zoster and simplex reactivation following COVID-19 vaccination: new insights from a vaccine adverse event reporting system (VAERS) database analysis. (4th May 2022) - Gringeri, Michele; Battini, Vera; Cammarata, Gianluca; Mosini, Giulia; Guarnieri, Greta; Leoni, Chiara; Pozzi, Marco; Radice, Sonia; Clementi, Emilio; Carnovale, Carla
ABSTRACT: Background: A few cases of Herpes Zoster and Simplex reactivation following COVID-19 immunization have been recently described, but the real extent of this suspected adverse event has not been elucidated yet. Methods: We performed a nested case/control study by using the U.S. Vaccine Adverse Event Reporting System database. We carried out a case-level clinical review of all Herpes reactivation cases following the administration of COVID-19 vaccines. For cases and controls, significance was set at P = 0.05, differential risk of reporting was assessed for each vaccine as reporting odds ratio and incidence was estimated based on the total number of vaccine doses administered. Results: Of 6, 195 cases included in the analysis (5, 934 and 273 reporting Herpes Zoster and Herpes Simplex, respectively) over 90% were non-serious. We found a slightly higher risk of reporting both for Zoster (ROR = 1.49) and Simplex (ROR = 1.51) infections following the Pfizer-BioNTech vaccine. The estimated incidence was approximately 0.7/100, 000 and 0.03/100, 000 for Zoster and Simplex, respectively. Conclusions: The paucity of cases (almost all of non-serious nature) makes the potential occurrence of this adverse effect negligible from clinical standpoints, thus supporting the good safety profile of the COVID-19 vaccination, which remains strongly recommended.